2023
DOI: 10.3389/fimmu.2023.1180900
|View full text |Cite
|
Sign up to set email alerts
|

The macrophage infectivity potentiator of Trypanosoma cruzi induces innate IFN-γ and TNF-α production by human neonatal and adult blood cells through TLR2/1 and TLR4

Abstract: We previously identified the recombinant (r) macrophage (M) infectivity (I) potentiator (P) of the protozoan parasite Trypanosoma cruzi (Tc) (rTcMIP) as an immuno-stimulatory protein that induces the release of IFN-γ, CCL2 and CCL3 by human cord blood cells. These cytokines and chemokines are important to direct a type 1 adaptive immune response. rTcMIP also increased the Ab response and favored the production of the Th1-related isotype IgG2a in mouse models of neonatal vaccination, indicating that rTcMIP coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Blockade of TLR2 resulted in more T. cruzi replication ( Figure 5A ) likely due to a reduction in TLR2-mediated signaling and cytokines production ( Figure 6 ). Interestingly, we have not detected significant overexpression of TLR4, reported to induce IFN-γ and TNF-α production in human cord blood cells after stimulation a recombinant T. cruzi macrophage infectivity potentiator (TcMIP) ( Ait Djebbara et al, 2023 ). Likewise, we have not observed an increase in the level of nuclear factor kappa B (NF-κB) RNA transcripts, a molecule shown to be activated in placental explants via TLRs signaling pathways ( Liempi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Blockade of TLR2 resulted in more T. cruzi replication ( Figure 5A ) likely due to a reduction in TLR2-mediated signaling and cytokines production ( Figure 6 ). Interestingly, we have not detected significant overexpression of TLR4, reported to induce IFN-γ and TNF-α production in human cord blood cells after stimulation a recombinant T. cruzi macrophage infectivity potentiator (TcMIP) ( Ait Djebbara et al, 2023 ). Likewise, we have not observed an increase in the level of nuclear factor kappa B (NF-κB) RNA transcripts, a molecule shown to be activated in placental explants via TLRs signaling pathways ( Liempi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 73%
“…T. cruzi molecules such as surface glycoinositolphospholipids (GPIs) and parasite DNA/RNA sequences can be sensed by TLRs ( Macaluso et al, 2023 ). In fact, several investigators have shown the significance and involvement of TLRs in the control of T. cruzi infection ( Caetano et al, 2011 ; Castillo et al, 2017b ; Queiroga et al, 2021 ; Ait Djebbara et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even Katalin et al reported that m 6 A modifications suppress the ability of RNA to stimulate TLR3, TLR7, and TLR8, 38 they did not uncover the m 6 A-regulated expression level of TLR2, and our findings fill this knowledge gap. In fact, TLR2 is regulated by various mechanisms like infection and gut microbes, [39][40][41] and we have just discovered that m 6 A might be a regulatory mechanism during the TM infection process. Previous studies have shown that YTHDC2 primarily regulates RNA degradation through m 6 A modification.…”
Section: Discussionmentioning
confidence: 99%
“…Transplacental transfer of sensitizing T. cruzi components from the infected mother to her fetus is another possibility [ 26 ], although molecules implicated have not yet been identified. As TNF-a expression is critically induced by histone methylation triggered by the TLR4 ligand LPS [ 31 ] and as T. cruzi expresses TLR4 ligands [ 32 , 33 ], we may wonder if such molecules might be transferred from the infected mother to prime fetal monocytes. We cannot discard the potential effect of IgG and/or T. cruzi -specific Abs transferred from the mother.…”
Section: Discussionmentioning
confidence: 99%